Planning Regional Logistics Infrastructure taking into account Cross-sector Partnership of Stakeholders and Sustainable Development Principles - Chevhanova, Vira; Yevdokymov, Andrii; Chortok, Yulija; Yevdokymova, Alona (International Journal of Engineering and Technology, 2018)
The objective of the study was to solve the pressing problem, which justify need for a responsible attitude of business and government towards society and the environment. The methods of determining the location of the logistics center as an object of the regional logistic infrastructure were used for this purpose, taking into account requirements and interests of all stakeholders and sustainable development principles. The methodology of the study was based on the authors’ analysis of foreign and Ukrainian publications, concerned with the formation of the regional logistics infrastructure and statements of the stakeholders’ social and environmental responsibility. The study has suggested the main principles of planning logistics infrastructure based on cross-sector partnership of stakeholders, which, in the authors’ point of view, would contribute to the sustainable development of the region and raise the level and efficiency of the regional logistics. A positive aspect of the paper was the results of analysis, namely the regional logistics center impact on the formation of sustainable development indicators in the region, the features and factors that determine the specifics of the Ukrainian regions transition to sustainable development and create preconditions for cooperation of stakeholders of different sectors such as community, business and authority.